How do safety professionals' influence managers within organizations? – A critical incident approach. (December 2021) - Madigan, Cassandra; Johnstone, Kelly; Way, Kïrsten A.; Capra, Mike
Highlights: Safety professionals use ten upward influence tactics, mainly rational persuasion (RP). Three new influence tactics emerged (coaching, storytelling, social proof). RP dominated in initial attempts; coalition and legitimating in follow-up attempts. Preparing for influence and positive relationships with managers enabled influence. Competing priorities, organizational culture, individual factors impede influence. Abstract: There has been increasing recognition that the ability to influence managers within organizations is a critical capability for safety professionals. Although safety decisions are made at all levels within an organization, those key safety decisions relating to strategies, priorities, operational procedures, and the allocation of resources are largely made by management. However, there is limited empirical research on how safety professionals direct influence upwards in organizations. In this paper, we investigate the specific influence behaviors/tactics employed by safety professionals for upward influence and the sequencing of tactic use for initial and subsequent influence attempts with the same manager. In addition, we identify the factors that safety professionals perceive either enable or hinder their ability to be strategically influential. We use the critical incident technique (Flanagan, 1954 ) to elicit both successful and unsuccessful influencing experiences from thirty safety professionals, employed in a range of industries across Australia and New Zealand. Qualitative analysis revealed rational persuasion was the dominant influencing strategy for initial attempts, while the coalition tactic was most frequently used in follow-up attempts. We also identified three new influence tactics that safety professionals used (coaching, storytelling, social proof) that were different from those described in traditional influence models. Further, factors that enable and hinder upward influence were generated from the critical incidences. This study extends existing theory and empirical research on how safety professionals direct influence upwards in organizations and proposes implications for safety practice and theory.